2022
DOI: 10.3389/fimmu.2022.1008390
|View full text |Cite
|
Sign up to set email alerts
|

“Rogue” neutrophil-subset [DEspR+CD11b+/CD66b+] immunotype is an actionable therapeutic target for neutrophilic inflammation-mediated tissue injury – studies in human, macaque and rat LPS-inflammation models

Abstract: Background and objectiveThe correlation (Rs > 0.7) of neutrophils expressing the dual endothelin1/signal peptide receptor (DEspR+CD11b+/CD66b+) with severity of hypoxemia (SF-ratio) and multi-organ failure (SOFA-score) in patients with acute respiratory distress syndrome (ARDS) suggest the hypothesis that the DEspR+ neutrophil-subset is an actionable therapeutic target in ARDS. To test this hypothesis, we conducted in vivo studies to validate DEspR+ neutrophil-subset as therapeutic target and test effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…Premised upon preclinical studies detecting a causal role of SARS CoV2 on NETformation and NET-forming neutrophils on capillary-tissue barriers, [8,9] this prospective study of patients with acute COVID-19 identified DEspR+[NET+Ns] as a mediator of multi-organ failure progression. These observations are supported by the causal role of NETs in direct endothelial cell injury demonstrated in ex vivo studies [8][9][10]30], and the causal role of DEspR in extending neutrophil lifespan [20]. We note that while causal mediation analysis has been previously used to evaluate inflammatory of the effect of obesity on risk for mortality in COVID-19 [31], and soluble RAGE receptor levels and angiopoietin-2-levels in sepsis-related ARDS [32,33], here we report causal mediation analysis of NET-forming neutrophil subsets.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Premised upon preclinical studies detecting a causal role of SARS CoV2 on NETformation and NET-forming neutrophils on capillary-tissue barriers, [8,9] this prospective study of patients with acute COVID-19 identified DEspR+[NET+Ns] as a mediator of multi-organ failure progression. These observations are supported by the causal role of NETs in direct endothelial cell injury demonstrated in ex vivo studies [8][9][10]30], and the causal role of DEspR in extending neutrophil lifespan [20]. We note that while causal mediation analysis has been previously used to evaluate inflammatory of the effect of obesity on risk for mortality in COVID-19 [31], and soluble RAGE receptor levels and angiopoietin-2-levels in sepsis-related ARDS [32,33], here we report causal mediation analysis of NET-forming neutrophil subsets.…”
Section: Discussionmentioning
confidence: 57%
“…Our recent studies have identified DEspR+CD11b+ neutrophils (DEspR+[Ns] from hereon), as a dysregulated "rogue" neutrophil-subset capable of NET-formation while in the circulation, extended survival, low-clearance, enhanced adhesion, and association with severity measures and mortality in COVID-19 acute respiratory distress syndrome (ARDS) [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Premised upon preclinical studies detecting a causal role of SARS CoV2 on NET-formation [ 8 ] and NET-forming neutrophils on capillary-tissue barriers, [ 8 , 9 ]this prospective study of patients with acute COVID-19 identified DEspR + [NET + Ns] as a mediator of multi-organ failure progression. These observations are supported by the causal role of NETs in direct endothelial cell injury demonstrated in ex vivo studies [ 8 10 , 30 ], and the causal role of DEspR in extending neutrophil lifespan [ 20 ]. We note that while causal mediation analysis has been previously used to evaluate inflammatory mediators of the effect of obesity on risk for mortality in COVID-19 [ 31 ], and soluble RAGE receptor levels and angiopoietin-2-levels in sepsis-related ARDS [ 32 , 33 ], here we report causal mediation analysis of NET-forming neutrophil subsets.…”
Section: Discussionmentioning
confidence: 77%
“…Our recent studies have identified DEspR + CD11b + neutrophils (DEspR + [Ns] from hereon), as a dysregulated “rogue” neutrophil-subset capable of NET-formation while in the circulation, extended survival, low-clearance, enhanced adhesion, and association with severity measures and mortality in COVID-19 acute respiratory distress syndrome (ARDS) [ 18 20 ]. Here, we test whether the putative “rogue” CD11b + DEspR + NET-forming neutrophil-subset, DEspR + [NET + N], mediates the worsening of early multi-organ dysfunction (measured by the Sequential Organ Failure Assessment [SOFA]-score [ 21 ] at timepoint-1) towards multi-organ failure (measured as higher SOFA-scores at a later timepoint-2), and/or mediates poor clinical outcomes (as measured by intensive care unit free days [ICUFD] by day-28) [ 22 ] in severe COVID-19 using causal mediation analysis.…”
Section: Introductionmentioning
confidence: 99%
“…195 This phenotype may be induced by CIRP. 196 Carstensen et al 197 demonstrated that inhibition of the DEspR + CD11b + neutrophil subset could alleviate multiple respiratory diseases. 198 While targeting the intervention of CD11b + CD18 + neutrophils would aggravate influenzainduced lung damage, the specific mechanism of which was related to affecting functions of T cells.…”
Section: Respiratory Diseasesmentioning
confidence: 99%